answersLogoWhite

0


Best Answer

ok well the answer i got to was y= -4.5, i came to that by subtsituting in 5 for the x value and solving for y i assumed everything was adding together since you didnt say otherwise. ill show my work now 3(5)+6y+12 =15+6y+12 =27+6y -27/6=6y/6 y=-4.5

User Avatar

Wiki User

15y ago
This answer is:
User Avatar

Add your answer:

Earn +20 pts
Q: Find the solution of 3x 6y 12 when x 5?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

Solve for y -3x plus 6y equals 12?

y-3x+6y=12 7y=3x+12 y=3x/7 +12/7


What is 3x plus 6y equals 12 in slope-intercept form?

3x + 6y = 12 Rearranging terms: 6y = -3x + 12 Divide through by 6: y = -1/2*x + 2


What is the ordered pair of 3x plus 6y equals 36 3x-6y equals 0?

3x + 6y = 363x - 6y = 0 add both equations6x = 36x = 63x - 6y = 03(6) - 6y = 018 - 6y = 018 = 6y3 = yThe solution point is (6, 3).


How do you turn 3x-6y equals 12 in slope intercept form?

3x-6y=12; subtract 12 & add 6y to both sides 3x-12=6y; divide by 6 (1/2)x-2=y; re-write y=(1/2)x-2 slope intercept form


Is 3x-6y equals 12 a parallel line?

It is a straight line. standard form is y = mx + b where m = slope 3x - 6y = 12 6y = 3x -12 y = .5x -2 any other line with slope = 0.5 would be parallel to it


What is 3x plus 6y plus 6x?

Well, darling, 3x plus 6y plus 6x simplifies to 9x + 6y. That's all there is to it, sugar. Math doesn't have to be complicated, just like your love life!


How do you get y by itself in the equation 3x-6y equals 9?

3x-6y=9 -3x -3x -6y=9-3x __ ____ -6 -6 y=9-3x ____ -6


The greatest monomail factor of 3x-6y plus 12?

3


What is the y-intercept of 3x-6y equals 72?

[ y = -12 ] is.


5x2 y equals 3x-6y as a function?

5x2y = 3x - 6y 5x2y + 6y = 3x y(5x2 + 6) = 3x y = (3x)/(5x2 + 6) This is a rational function.


What is 3x-6y equals 9 in slope-intercept form?

3x - 6y = 9Subtract 3x from each side:-6y = -3x + 9Multiply each side by -1 :6y = 3x - 9Divide each side by 6:y = 0.5x - 1.5


How do you solve 6y-3x-9(1-1)?

6y-3x-9(1-1)=6y-3x-9(0)=6y-3x-0=6y-3xOnly like terms can be simplified. A like term has the same variables, X and Y are different variables. 6y-3x cannot be simplified because they are not like terms.